THE STOMACH - Murodullayev Khumoyun Izzatillo o’g’li; Pardayev Dilmurod Shermuhammadovich; Musurmonova Marjona Samandar qizi; Khasanov Farrukhjon Sherali o‘g‘li (TADQIQOTLAR, 2025)
Abstract:  Role  of  the  digestive  tract  in  the  digestive  system.  Anatomical, physiological and histological structure of the stomach. Relationship between them and the extent to which they are bounded by the body. Information about infectious and non-infectious  diseases  of  the  stomach  at  present.  In  what  countries  are  the  most common stomach diseases in the world? How many people suffer from such illnesses and  how  many  percent  of  annual  deaths.  Measures  to  combat  the  diseases  of  the digestive system in the world.